Medical device maintenance outsourcing: Have operation management research and management theories forgotten the medical engineering community? A mapping review (2012)
In this paper, we examine the large body of existing research on outsourcing, and assess the status of research on outsourcing the maintenance of medical devices. Because so little research in this area currently exists, the study was broadened to include other fields that outsource maintenance services, and considers possible applications to the field of medical device maintenance. In all, this paper examines 55 articles spanning various dimensions, including: mathematical models, empirical studies, and conceptual papers. We conclude that research into the outsourcing of medical device maintenance services in hospitals is still in its infancy stages, and that further progress in this field would benefit from additional empirical study grounded in management theory. © 2012 Elsevier B.V. All rights reserved.